2014
DOI: 10.1364/ol.39.006438
|View full text |Cite
|
Sign up to set email alerts
|

Thermal regenerated grating operation at temperatures up to 1400°C using new class of multimaterial glass-based photosensitive fiber

Abstract: The work demonstrates for the first time a thermal regenerated grating (RG) operating at an ultra-high temperature up to 1400°C. A new class of photosensitive optical fiber based on erbium-doped yttrium stabilized zirconia-calcium-alumina-phospho silica (Er-YZCAPS) glass is fabricated using modified chemical vapor deposition (MCVD) process, followed by solution doping technique and conventional fiber drawing. A type-I seed grating inscribed in this fiber is thermal regenerated based on the conventional thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The maximum temperature sensitivity of 33.4 pm/°C is achieved at the temperature around 1000 °C for the sensor after being annealed at 1005 °C , which is over two times higher than many temperature sensors reported recently [9,13,17]. It is noted that the measured maximum sensitivity is larger than our theoretically calculated temperature sensitivity of 25 pm/°C , this is possibly because the TOC () of the HCF cladding is temperature dependent and it has a higher value of  at high temperatures.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The maximum temperature sensitivity of 33.4 pm/°C is achieved at the temperature around 1000 °C for the sensor after being annealed at 1005 °C , which is over two times higher than many temperature sensors reported recently [9,13,17]. It is noted that the measured maximum sensitivity is larger than our theoretically calculated temperature sensitivity of 25 pm/°C , this is possibly because the TOC () of the HCF cladding is temperature dependent and it has a higher value of  at high temperatures.…”
Section: Resultsmentioning
confidence: 65%
“…By utilizing an intensive UV laser source or femtosecond pulse duration infrared (fs-IR) laser source, other types of gratings can be inscribed. The working temperature of these kinds of grating sensors can be extended to over 1000 °C [7][8][9]. However, the fabrication process for such gratings is rather complicated and expensive [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, an ultra-high temperature RG in boron-codoped germanosilicate optical fiber using 193 nm ArF excimer laser over 1000 ℃ was presented by Bandyopadhyay et al [8]. Yang et al demonstrated the RG inscribed in new glass composition-based photosensitive fiber with temperature resistance up to 1400℃ [9]. Our earlier investigation [10] has proven that the pre-treatment process has a profound impact on the performance of the RG in terms of temperature resistant and durability.…”
Section: Introductionmentioning
confidence: 88%
“…In general, a typical SHM system comprises the integration of sensor techniques [1], smart materials, data interrogation and transmission, computational power, and processing ability inside the structures. Among these components in an SHM system, sensor technique plays an important role in monitoring not only the structural status—such as stress, displacement, acceleration, and vibration [2,3,4]—but also the influential environment parameters, for instance, wind speed, temperature, and others [5,6]. Reinforced concrete (RC) beam vibration detection provides tremendous information that indicates the health of a building.…”
Section: Introductionmentioning
confidence: 99%